Seismic resistance of the corroded bimetallic steel bar under different strain amplitudes. (14th February 2022) - Hua, Jianmin; Fan, Haifeng; Yan, Wei; Wang, Neng; Xue, Xuanyi; Huang, Lepeng
Highlights: Low-cycle fatigue properties of BSB specimens with different corrosion ratios are investigated experimentally. Predictive equations are proposed to clarify effects of corrosion ratio and fatigue strain amplitude. Failure morphologies of corroded BSB specimens under different low-cycle fatigue loadings are discussed. Abstract: To evaluate seismic resistance of concrete structures with bimetallic steel bars (BSBs) over the entire life cycle, it is important to clarify effects of corrosion ratio and fatigue strain amplitude on low-cycle fatigue properties. The experimental results of this study indicated that corrosion had little effect on the shape of hysteretic curve of BSB specimens. Increases in the fatigue strain amplitude and corrosion ratio decreased the cycles to failure and total energy densities. For BSB specimens with ε = 0.6%, the stable stage in maximum stress curves gradually decreased with an increase in corrosion ratio. With increases in fatigue strain amplitude and relative number of cycles, the plastic strain range and plastic and elastic strain ratio increased. The effects of fatigue strain amplitude on low-cycle fatigue properties of the BSB specimens were significantly higher than those of the corrosion ratio. Predictive equations were suggested to quantify the effects of the fatigue strain amplitude and corrosion ratio on the cycles to failure and total energy density. For BSB specimens with ε = 0.6%, fracture source zones, fracture developing zones, and fracture zones could be observed. No obvious separation was found between the stainless steel cladding layer and the carbon steel substrate. When ε = 1.5 and 2.4%, the arc line in the fracture developing zone barely disappeared. There were separations between the cladding layer and the substrate. Furthermore, radial cracks were observed near the stainless steel cladding layer.